Holocene history of the landscape at the biogeographical and cultural crossroads between Central and Eastern Europe (Western Podillia, Ukraine). (15th July 2022) - Hájková, Petra; Petr, Libor; Horsák, Michal; Jamrichová, Eva; Roleček, Jan
Abstract: Continentality is a globally significant gradient influencing broad-scale biogeographical patterns. An excellent example is the transition from the European temperate forest biome to the continental steppe and forest-steppe of Eurasia. One of the biogeographic crossroads where the two biomes meet is the Western Podillia in the western part of Ukraine. It is known for its rich biodiversity with a mixture of steppe, forest and montane species, despite a relatively humid climate suitable for closed-canopy forests. Biologists have postulated the refugial character of the local steppes, but a modern paleoecological reconstruction of the environmental history of the region has been lacking. We fill this gap here with a multi-proxy study (pollen, plant and mollusc macrofossils, microcharcoal, geochemistry) of two profiles sampled in calcareous fens adjacent to species-rich steppe grasslands. To link the reconstructed environmental history with the history of human settlement, we compiled available archaeological records from the studied region. Together, the analyzed profiles cover the entire Holocene and the end of the Last Glacial period, as shown by high-quality age-depth models. All studied proxies support the hypothesis that an open or semi-open landscape existed in Western Podillia during the Holocene. The complete absence of wood remains in Holocene sediments, and the persistence of fen specialists showed the exceptional long-term stability of open wetlands. The continuous presence of pollen of light-demanding plants, low abundance of closed-canopy trees compared to open-canopy trees, and stable concentrations of geochemical indicators of erosion suggest a semi-open landscape with a mosaic of forests, steppe grasslands, and other open habitats. Multivariate analysis revealed the similarity of pollen assemblages with sites in the forest-steppe zone at the interface between the Pannonian Basin and the Western Carpathians. The continuous presence of non-woody microcharcoal in high abundance suggests a role of fire in maintaining open habitats, and the archaeological record provides evidence of human activity throughout the Holocene near the study sites. Comparison with modern pollen spectra suggests that the landscape was probably somewhat more forested in the past than today, but rather by open-canopy trees. Our results indicate that Western Podillia has become a biogeographic crossroads not only because of its location on the border between Central and Eastern Europe, but also because of the unusual combination of relatively humid climate and continuity of open or semi-open landscapes since the Last Glacial. Highlights: Long-term continuity and mild climate shaped biodiversity of Western Podillia. Prehistoric human and fires may have contributed to the maintenance of open landscape. Open-canopy trees prevailed in the forests during the Holocene. Several proxies show exceptional stability of open calcareous wetlands.